2016
DOI: 10.19128/turje.267924
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenlerin işe angaje olmalarında demografik özelliklerinin rolü

Abstract: The aim of this study is to reveal the impact of demographic features on teachers'work engagement. The sample of the study consists a total of 433 primary school and branch teachers working at primary and secondary schools located within the province of Kahramanmaraş during the academic year of 2014-2015. Path analysis was conducted using structural equation modeling in the study. The findings showed that the model was found to be statistically significant (CFI=0.94; TLI=0.92; RMSEA=0.06; SRMR=0.04). The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
4
0
6
Order By: Relevance
“…The Work Engagement Scale was then reduced to one dimension in a study conducted by Köse (2016b). Thus, the present study has deployed one-dimensional form of the scale, which was adapted by Köse (2016b). The reliability coefficient was found to be 0.94 for the overall scale.…”
Section: Work Engagement Scalementioning
confidence: 96%
See 4 more Smart Citations
“…The Work Engagement Scale was then reduced to one dimension in a study conducted by Köse (2016b). Thus, the present study has deployed one-dimensional form of the scale, which was adapted by Köse (2016b). The reliability coefficient was found to be 0.94 for the overall scale.…”
Section: Work Engagement Scalementioning
confidence: 96%
“…Köse (2015) has indicated that the items in the scale were collected under 2 dimensions (Professional attitude-Professional enthusiasm) considering the factor analysis. The Work Engagement Scale was then reduced to one dimension in a study conducted by Köse (2016b). Thus, the present study has deployed one-dimensional form of the scale, which was adapted by Köse (2016b).…”
Section: Work Engagement Scalementioning
confidence: 99%
See 3 more Smart Citations